Dumping PowerPoint In Favor of Web Sites - Bower, Timothy L. (My University, 2011)
This paper describes how comprehensive web sites (online study guides) are being used as a tool to deliver course material. Such a delivery tool may not be needed for all courses, but feedback from students suggests that web pages provide improved delivery of course material. Students report that having a complete site with all course material presented in hierarchical order with links to related internal and external material gives the course more structure and that the material is more convenient to access. Although the specific software tool used to create these study guides is held in high regard, the intent is to present the value of online study guides as a teaching tool rather than the merits of a specific program. Other educators may prefer to use a different program to develop study guides. While teaching an online class, a new software tool was used to facilitate the development of a web site containing the course material. The objective was to provide additional instruction and reference material to compensate for not being with the students in person. Although the students had the textbook and recorded lectures with accompanying slides (PowerPoint), an additional resource seemed to be needed to guide them through the course material. Similar web sites were later developed for three traditional classroom courses. In these classes, the course material web sites were called online study guides. A study guide falls between a textbook and lecture slides in terms of the level of detail to the material presented.
Keywords: PowerPoint; Instructional Technology; T385; LB1028